Home care services for older clients with and without cognitive impairment in Sweden. (30th July 2018) - Sandberg, Linda; Nilsson, Ingeborg; Rosenberg, Lena; Borell, Lena; Boström, Anne‐Marie
Abstract: Little is known about the types of home care services granted to older clients in Sweden. The objectives of this study were to: (a) identify and describe the range of granted home care services and service hours; (b) compare services granted for clients with and without documented cognitive impairment; and (c) examine associations between the range of granted home care services and factors related to cognitive impairment and demographical characteristics. The study design was descriptive and cross‐sectional. The data, included records of granted home care services for clients age 65+ with ( n  = 43) and without ( n  = 88) cognitive impairment documented by the local municipality assessors, collected from one agency in Sweden during a 2‐month period in 2015. Data analyses resulted in an overview of the range of home care services divided into two categories: personal care and service. In the personal care category, the median was 3 for types of services (range 0–12), and shower ( n  = 69; 52.7%) was the most common service. In the service category, the median was 5 for types of services (range 0–10), and cleaning the household ( n  = 103; 78.6%) was the most common service. The median for service hours was 27 hr per month (range 2.5–127.5). Logistic regression models revealed that cognitive impairment was associated with a higher number of services in the personal care category and a higher number of hours per month. Living alone was associated with a higher number of services in the service category. In conclusion, a wide range of home care services were provided for clients who have complex needs in daily life. Home care services were granted to clients with cognitive impairment and to a greater extent with clients who were living alone.